Respuesta :
Answer:
X=-3
Step-by-step explanation:
So let’s multiply it out, 2x-6+9=3x+3+x. So 2x-3=4x+3. So 2x+3=-3. 2x=-6 and so x=-3.
Answer: The required value of x in the give equation is 0.
Step-by-step explanation: We are given to find the value of x in the following equation :
[tex]2(x-3)+9=3(x+1)+x~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]
To find the value of x, we must solve the given equation.
From equation (i), we have
[tex]2(x-3)+9=3(x+1)+x\\\\\Rightarrow 2x-6+9=3x+3+x\\\\\Rightarrow 2x+3=4x+3\\\\\Rightarrow 4x-2x=3-3\\\\\Rightarrow 2x=0\\\\\Rightarrow x=\dfrac{0}{2}\\\\\Rightarrow x=0.[/tex]
Thus, the required value of x in the give equation is 0.